PERISTIWA GERBONG MAUT BONDOWOSO SEBAGAI SUMBER IDE KEKARYAAN KARYA SENI LUKIS - Bawon, Mohammad Imam; Rusputranto, Albertus (TEXTURE Art and Culture Journal, 2024)
This artistic research entitled “The Death Carriage Incident in Bondowoso as a Source of Ideas for Painting Works” is a response to my experience of hearing and reading the historical story of the Bondowoso people’s struggle. The death carriage incident is a sad story of the Bondowoso people’s struggle with their fighters. The story of the mass arrests carried out by the Dutch aggressors against the people and fighters of Bondowoso, to the point that the prisons in Bondowoso were no longer able to accommodate the prisoners. As a result, the Dutch army transferred prisoners using trains (three goods cars to transport the prisoners) from Bondowoso station to Surabaya station which then led to a tragedy known as the Bondowoso death carriage incident. The purpose of this creative research is to create works of painting that originate from the Bondowoso death carriage incident. This paper will explain the concept of creation, method of creation, process of creation and description of the works of painting that were created. The concept of the creation of this final assignment expresses the depiction or scene of the events of the Bondowoso death carriage incident, with the depiction obtained from my imagination based on the data obtained. The emergence of imagination or images in my mind became the starting point for the emergence of creative ideas which were then expressed in romanticism-style paintings. The method of creating the work refers to Francisco Goya's method of creation. The method consists of three stages, namely: the first stage, collecting sources of ideas or information; the second stage, developing initial ideas by describing what is obtained from information or personal experience, and combining the data received with imagination; the third stage, visualizing ideas and imagination into the media. This artistic research produces romanticism-style paintings using a combination of acrylic and oil paints on canvas media.